Improving data entry in basketball analysis user interface using HCI usability principles / Hadzri Harman - Harman, Hadzri (2012)
Basketball Analysis Software is created to capture data in basketball game such as score, foul and rebound. The outcome of this system is to produce a statistic. User need to observe the game and input the data based on what they see. Eventually, user miss capture the data and make error during using the software. Thus it will produce an inconsistent and inaccurate statistic. The problem occur when user miss capture the data because of doing the data entry process for the previous data. In order to solve this problem, an improvement on the data entry user interface using HCI usability design is needed. The project objective is to identify the current task analysis, analysis the task analysis and design the new data entry user interface of the basketball analysis software. The scope of the project consists of project selection and planning, analysis, design and evaluation phase. While doing the research, the researcher focus on the five principle in HCI usability design which is efficiency, memorability, learnability, satisfaction and less error. The evaluation process also will base on the efficiency, satisfaction and error criteria.